Sharia Management in Various Sectors: Concepts, Principles, Functions, and Challenges - Chamala Syefa, Mutiara (Sharia Business Management Department of STEBIS Bina Mandiri, 2025)
This study discusses the concepts, principles, functions, and applications of sharia management in various sectors, as well as the challenges and prospects in the future. Sharia management is based on the teachings of the Qur'an, Hadith, ijma', and qiyas, emphasizing justice, transparency, and blessings in resource management. In Indonesia, the sharia-based economy has experienced rapid growth, driven by government policies and sharia financial institutions. This research uses a literature review method to analyze the application of sharia management principles, including aspects of planning, organizing, leadership, and control in business, education, and government sectors. The results of this analysis are expected to contribute both theoretically and practically to the development of sharia management in line with Islamic values.